2021
DOI: 10.1093/noajnl/vdab046
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion G protein-coupled receptors in glioblastoma

Abstract: Members of the adhesion family of G protein-coupled receptors (GPCRs) have received attention for their roles in health and disease, including cancer. Over the past decade, several members of the family have been implicated in the pathogenesis of glioblastoma. Here, we discuss the basic biology of adhesion GPCRs and review in detail specific members of the receptor family with known functions in glioblastoma. Finally, we discuss the potential use of adhesion GPCRs as novel treatment targets in neuro-oncology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 131 publications
1
13
0
Order By: Relevance
“…For example, given our discovery that GPR133 is required for GBM growth, engineering inhibitory anti-GPR133 antibodies would lay the foundation for testing effects on tumor biology (21). Alternatively, given the de novo expression of GPR133 in GBM relative to healthy non-neoplastic brain tissue, anti-GPR133 internalizing antibodies could be used to deliver antibody-drug conjugates to GBM cells (21,28,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, given our discovery that GPR133 is required for GBM growth, engineering inhibitory anti-GPR133 antibodies would lay the foundation for testing effects on tumor biology (21). Alternatively, given the de novo expression of GPR133 in GBM relative to healthy non-neoplastic brain tissue, anti-GPR133 internalizing antibodies could be used to deliver antibody-drug conjugates to GBM cells (21,28,34).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, given the de novo expression of GPR133 in GBM relative to healthy non-neoplastic brain tissue, anti-GPR133 internalizing antibodies could be used to deliver antibody-drug conjugates to GBM cells (Bayin et al, 2016;Frenster et al, 2020;Stephan, Ravn-Boess, & Placantonakis, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular functions of aGPCRs such as cell adhesion, migration, cell polarity, and guidance are highly relevant for tumor cell biology. Consistently, members from all aGPCR groups are associated with cancer, for example, GPR56/ADGRG1, CD97/ADGRE5, GPR133/ADGRD1, ELTD1/ADGRL4, GPR110/ADGRF1, GPR116/ADGRF5, BAI1/ADGRB1, GPR124/ADGRA2, and GPR125/ADGRA3 [161‐167]. For some of these aGPCRs, there is evidence for incorrect expression or changes in receptor activity (e.g., VLGR1/ADGRV [168], GPR133/ADGRD1 [169], and LPHN/ADGRL [170]), whereas for others, detailed knowledge exists about the molecular role they play in tumorigenesis (e.g., CD97/ADGRE5 [34,171,172], ADGRF5/GPR116 [173,174], GPR56/ADGRG1 [51,175,176,177], BAI1/ADRGB1 [178‐180], GPR124/ADGRA2 [181], and GPR125/ADGRA3 [182]).…”
Section: Clinical Aspects Of Agpcr Function and Potential Therapeuticsmentioning
confidence: 99%
“…It has been demonstrated that GPCRs bind ligands from the ECM or plasma membrane of adjacent cells, causing conveying cell–cell or cell–matrix interactions [ 47 ]. The activation of a receptor thorough binding with a ligand leads to changes in cellular processes, including cell migration, proliferation, neoangiogenesis and invasion of GBM [ 48 ]. Moreover, GPCR could be targeted for GBM therapies because of their role in controlling tumor pathogenesis through molecular interactions with oncogenic signaling pathways [ 48 ].…”
Section: A Disintegrin and Metalloproteinase (Adam)—general Informationmentioning
confidence: 99%
“…The activation of a receptor thorough binding with a ligand leads to changes in cellular processes, including cell migration, proliferation, neoangiogenesis and invasion of GBM [ 48 ]. Moreover, GPCR could be targeted for GBM therapies because of their role in controlling tumor pathogenesis through molecular interactions with oncogenic signaling pathways [ 48 ]. In addition, several ADAMs are kept in an inactive state via the interaction of a cysteine residue with zinc at the propeptide domain in the metalloproteinase module.…”
Section: A Disintegrin and Metalloproteinase (Adam)—general Informationmentioning
confidence: 99%